2004
DOI: 10.3141/1897-24
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Safety Benefits of Variable Speed Limits

Abstract: A method is suggested for evaluating the effectiveness of variable speed limits in reducing freeway crash potential. The real-time crash prediction model that was developed in earlier studies was used to estimate crash potential for different control strategies of variable speed limits. To mimic realistic responses of drivers to changes in speed limits, a microscopic traffic simulation model was used. The simulation results indicate that total crash potential over the entire freeway segment could be significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 11 publications
(13 reference statements)
3
56
0
Order By: Relevance
“…Studies by Allaby et al (2007) and Lee et al (2004) showed that safety was improved at the expense of increase in travel time, However studies by Habtemichael and Picado-Santos (2013) and Islam et al (2013) showed improvements in mobility as well as safety after implementation of VSL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Allaby et al (2007) and Lee et al (2004) showed that safety was improved at the expense of increase in travel time, However studies by Habtemichael and Picado-Santos (2013) and Islam et al (2013) showed improvements in mobility as well as safety after implementation of VSL.…”
Section: Discussionmentioning
confidence: 99%
“…Impacts of VSL on Safety Lee et al (2004) employed a real-time crash prediction model integrated with a PARAMICS micro-simulator to evaluate a speed-based VSL algorithm. They concluded that total crash potential was reduced at the expense of increase in total travel time.…”
Section: Simulation Based Studies On Vslmentioning
confidence: 99%
“…) was modified in 2003 [15], and then in 2004 [16] by the author and implemented in the simulation of a smaller transport network, 2.5 km long, which contains four inductive loops, three variable message signs and three traffic lanes. As a conclusion of the said simulation, the obtained results show that the average crash potential is reduced by approximately 25% by using the system of variable traffic signs and the crash prevention model.…”
Section: Overview Of Previous Researchmentioning
confidence: 99%
“…The models [16,18,20] and research [5,6,14] were made on the so called urban motorways which have from 6 to 12 traffic lanes on average. In the same way, the existing models of accident occurrence prevention are adjusted to technical characteristics of such roads so the traffic volume change on the particular lane was taken into consideration as an important factor, as well as lane change frequency, area of the ramp for merging and exclusion, sections with increase or decrease of number of lanes etc.…”
Section: Overview Of Previous Researchmentioning
confidence: 99%
“…Borrough [5] and Lee et al [6] also reported possible decrease in the number of crashes as a result of applying VMS. Other researchers reported positive effect of VMS on reducing travel time, alleviating congestion and improving system performance [7,8,9].…”
Section: Introductionmentioning
confidence: 99%